Manual de conservação das paginações das calçadas em ladrilho hidráulico de Santa Maria/RS - Ongaratto, Eduardo (2018)
This Term Paper presents a study about the sidewalk’s surface hydraulic floor tiles layout in Santa Maria city/RS, resulting in a manual for conservation of this layout. It is a historical and comparative research in a delimited area of the city, Rio Branco Avenue and Acampamento Street. In this sample were identified fourteen pattern modules on the sidewalks, composed by four different square pieces (20 x 20 cm) of all-white, all-black, black and white and red and white. The floor tile units show a textured surface, providing the necessary adherence in an external environment, being the mixed pieces divided equally by two right triangles (20 cm equal catheti) connected by their hypotenuse. To subsidize information for the manual a bibliographical review about the following items was conducted: cultural heritage, the importance of sidewalks from world context to local context; sidewalks as cultural goods; theme connected concepts; and finally manuals and booklets available about the subject. It was also presented a rapid santa-marian historical contextualization, in which was possible to demonstrate the cultural and regional importance they possess. The legislation about responsibility in maintenance and execution of sidewalks was exposed and revealed that the city’s competence is delegated to the landlords. To get closer to the language used in a manual, which possess mainly a didactic, practical and objective purpose, it was included technical information about material specifications and good building technique for its execution, costs scene and where to purchase the tiles and, still, a step-by-step of stages to ensure that the tiles replacement (worn down or loose tiles) is executed in the original position or in a compatible fashion respecting the layout. Many concepts and rulings were exposed in the forms of myths or truths, aiming to facilitate the understanding of matters that usually concentrate nonconformities. At last, it was possible to conclude that a layout hydraulic tile’s sidewalk manual contributes to their conservation.